Effectiveness of ultrasound pretreatment on dried plant-based food quality: A meta-analysis - Yulni, Tri; Nelwan, Leopold Oscar; Suro Mardjan, Sutrisno; Manalu, Lamhot Parulian; Lestari, Nunik; Hartono, Lusiana Kresnawati; Agusta, Waqif; Mariastuty, Tantry Eko Putri; Pratama Astin, Eko; Garusti, Garusti (Agriculture and Natural Resources, 2026)
Importance of the work: Ultrasound has promising potential for pretreatment to enhance drying quality; however, there is a lack of quantitative synthesis across commodities and conditions. Objectives: To assess the effectiveness of ultrasound pretreatment on dried plant-based products and to investigate the effects of commodity category, ultrasound pretreatment (UP) parameters and drying parameters based on subgroup analyses. Materials and Methods: A meta-analysis of 55 Scopus-indexed studies was conducted using OpenMEE and applying Hedges’d and a random-effects model. The key quality parameters analyzed were color, rehydration ratio (RR), flavonoids (TFC), phenolics (TPC), vitamin C, antioxidant capacity based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant assay and water activity (Aw). Subgroup analyses examined commodity category, as well as ultrasound and drying parameters. Results: Ultrasound pretreatment significantly (p < 0.05) improved most quality parameters, except DPPH and vitamin C. Large effect sizes were observed for RR (3.339), TFC (2.093), TPC (0.876) and Aw (–2.096). High heterogeneity (inconsistency index >75%) indicated substantial inter-study variability, necessitating subgroup analyses. These analyses confirmed that commodity categories, ultrasound pretreatment parameters (equipment, sample-to-water ratio, frequency, power, duration, temperature) and drying parameters (method and temperature) significantly influenced UP effectiveness. Main finding: UP consistently improved multiple quality parameters, especially color stability, rehydration ratio, bioactive compound retention and water activity. Subgroup analysis revealed that treatment using 28 kHz, 300 W and 30°C for 30 min, followed by hot-air drying at 60°C, was particularly favorable for enhancing the drying quality of low-porosity root crops